Les quatre saisons du Renouveau charismatique, 1967–2017. (June 2019) - Aubourg, Valérie
This article focuses on the Catholic Charismatic Renewal. I study its development since 1967 to the current day, in the prism of its relationship with Pentecostalism. I identify four 'seasons', in other words four historical periods: the flourishing years (1972–1982 ) during which the Pentecostal experience penetrates into Catholicism; an identity retreat (1982–1997), a period of rapprochement with neo-Pentecostalists in order to resuscitate the Renewal (since 1997); and a final, 'post-charismatic' stage corresponding to the broader introduction of characteristic elements of Pentecostalism in Catholicism.